INTERNAL AUDIT PROCESSES IN NIGERIAN TAX ADMINISTRATION: A QUALITATIVE STUDY OF FIRS AUDITORS - Gurama, Zakariya’u (Kashere Journal of Management Sciences, 2025)
This study explored the internal audit processes required in tax administration to enhance auditors’ performance in adding value to Nigerian tax administration. The study is a qualitative study that employed interviews to gather data from internal auditors of tax administration. The empirical data were gathered from 9 internal auditors of the Federal Inland Revenue Service Headquarter Abuja, Nigeria. The gathered data were further transcript verbatim and analyzed for thematic purpose using Nvivo13 software. The findings of the study revealed that internal audit processes in tax administration have four interconnected components namely; planning, performing, communicating, and monitoring. These components are the auditor’s requirements that can facilitate the auditing activities and functions of auditors during auditing performance. Based on the findings, internal auditors are expected to consolidate these audit components to achieve the auditing processes proficiently. The findings of this study have practical implication for both tax administration and internal auditors in other public sector organization. Therefore, this study recommends that tax administrators should provide the entire required enabling environment to empower internal auditors to perform auditing functions objectively.